2016
DOI: 10.17221/294/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Agrarian import ban and its impact on the Russian and European Union agrarian trade performance

Abstract: Th e main objective of the paper is to identify the impact of the Russian agrarian import ban on imports of certain agricultural products from Europe, Norway, Canada, the USA and Australia. Th e import ban particularly aff ected the import of competitive agricultural and foodstuff commodities into Russia. Th e ban was the result of the political and security tensions existing between the Russian Federation and the Western World, since early 2014. If we take into consideration the volume of the mutual trade and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Disclosure of information about continuity of functioning is suggested in comments to accounting (financial) reports and remarks about financial condition of the company divided into reliability classes are provided in view of the table (Table 6). Changes in financial condition of milk processing agricultural companies over considered period are caused by some internal and external factors such as global economic crisis, sanctions [17] and embargo of import of milk products into the Russian Federation. These factors result in decreased benefit and earning capacity of the company making its financial condition worse.…”
Section: Resultsmentioning
confidence: 99%
“…Disclosure of information about continuity of functioning is suggested in comments to accounting (financial) reports and remarks about financial condition of the company divided into reliability classes are provided in view of the table (Table 6). Changes in financial condition of milk processing agricultural companies over considered period are caused by some internal and external factors such as global economic crisis, sanctions [17] and embargo of import of milk products into the Russian Federation. These factors result in decreased benefit and earning capacity of the company making its financial condition worse.…”
Section: Resultsmentioning
confidence: 99%
“…Wysokinski and Baran (2014), for example, reported the values and shares of the food and agricultural product exports from the EU to Russia before and after imposition of the embargo. Smutka et al (2016) analysed the most affected product groups and products in terms of the food self-sufficiency ratio and import dependency ratio in various EU countries. Their results indicated that the ban definitely affected individual industries and individual countries of the EU.…”
Section: Russian Food Import Banmentioning
confidence: 99%
“…One of such mechanisms, according to the authors, is the formation of «Local food systems» and «Alternative agro-food networks» operating within their framework. Both concepts are associated with the creation of conditions for fast (preferably without intermediaries) access of consumers to local food and are considered from the perspective of new models of interaction between producers, suppliers and consumers, based, on the one hand, on individual socio-economic, natural-climatic and other characteristics of specific territories and, on the other hand on the desire to avoid displacement of local food producers from the market [11][12], their support in order to achieve a higher level of self-sufficiency and reducing dependence on imports [13]. The operation of alternative agro-food networks is connected with the boundaries of the geographical area ranging from 50 km to 100 km from the point of their production [14].…”
Section: Brief Literature Reviewmentioning
confidence: 99%